The effects of season (spring versus autumn) on diagnosis of normocalcemic primary hyperparathyroidism - Basińska-Lewandowska, Magdalena; Lewiński, Andrzej; Lewandowski, Krzysztof C.; Skowrońska-Jóźwiak, Elżbieta (Frontiers in Endocrinology, 2022)
Background: Raised parathormone (PTH) in the setting of normal calcium concentrations can be observed both in normocalcemic primary hyperparathyroidism (nPHPT) and in secondary hyperparathyroidism, e.g. due to vitamin D deficiency. We assessed the effects of season (spring versus autumn) on the validity of diagnosis of potential nPHPT. Material and Methods: We measured concentrations of 25-OH-vitamin D, PTH, creatinine and total calcium in 125 healthy, subjects, age range 6-50, not taking any vitamin D supplements, in spring and in autumn. Results: In autumn there was an increase in vitamin D concentrations (p<0.001) and a decrease in PTH (p<0.001), and no change in calcium levels. Raised PTH concentrations were noted in 10 subjects in spring (8%) and in 6 subjects (4.8%) (p<0.05) in autumn. In spring, however, eight out of ten of these subjects (80%) had vitamin D <20 ng/ml, versus one in six (16.7%) in autumn (p<0.01). Furthermore, normalization of PTH was observed in seven out ten subjects (70%) who had raised PTH concentrations in spring. Conclusions: In spring raised PTH concentrations in the setting of normocalcemia are more likely to be caused by vitamin D deficiency rather by primary hyperparathyroidism. In contrast, in autumn, raised PTH concentrations are more likely to reflect normocalcemic primary hyperthyroidism. We postulate that screening for nPHPT should not be done in autumn rather than in spring.